Chính sách tiền tệ và sự điều chỉnh đầu tư công ty - Phùng Đức , Nam; Nguyễn Thị Diễm , Kiều (JOURNAL OF ASIAN BUSINESS AND ECONOMIC STUDIES, 2021)
This study explores the moderating role of monetary policy in corporate investment adjustment from the perspective of asymmetry under different policy states and heterogeneous impacts on companies with different cash holding levels. The asymmetric impact of monetary policy on corporate investment adjustment is found significant through both the credit and money channels of transmission. However, there are remarkable differences in the effects of these channels during expansionary monetary policy periods. The results also show that the impact of monetary policy on firm investment adjustment is significantly decreased in companies with higher cash holding levels, indicating the important role of cash holding in mitigating the effect of external environments. This result provides one of the first pieces of evidence for the heterogeneous impact of monetary policy on investment adjustment across firms with different characteristics.